Molecular Basis of Growth Inhibition by Acetate of an Adenylate Cyclase-Deficient Mutant of Corynebacterium glutamicum - Wolf, Natalie; Bussmann, Michael; Koch-Koerfges, Abigail; Katcharava, Nino; Schulte, Julia; Polen, Tino; Hartl, Johannes; Vorholt, Julia A.; Baumgart, Meike; Bott, Michael (Frontiers in Microbiology, 2020)
In Corynebacterium glutamicum, cyclic adenosine monophosphate (cAMP) serves as an effector of the global transcriptional regulator GlxR. Synthesis of cAMP is catalyzed by the membranebound adenylate cyclase CyaB. In this study, we investigated the consequences of decreased intracellular cAMP levels in a ΔcyaB mutant. While no growth defect of the ΔcyaB strain was observed on glucose, fructose, sucrose, or gluconate alone, the addition of acetate to these growth media resulted in a severe growth inhibition, which could be reversed by plasmid-based cyaB expression or by supplementation of the medium with cAMP. The effect was concentration-and pH-dependent, suggesting a link to the uncoupling activity of acetate. In agreement, the ΔcyaB mutant had an increased sensitivity to the protonophore carbonyl cyanide m-chlorophenyl hydrazone (CCCP). The increased uncoupler sensitivity correlated with a lowered membrane potential of acetate-grown ΔcyaB cells compared to wild-type cells. A reduced membrane potential affects major cellular processes, such as ATP synthesis by F1FO-ATP synthase and numerous transport processes. The impaired membrane potential of the ΔcyaB mutant could be due to a decreased expression of the cytochrome bc1-aa3 supercomplex, which is the major contributor of proton-motive force in C. glutamicum.